A new type of compositionally complex M5Si3 silicides: Cation ordering and unexpected phase stability. (15th April 2022) - Shivakumar, Sashank; Qin, Mingde; Zhang, Dawei; Hu, Chongze; Yan, Qizhang; Luo, Jian
Highlights: A new type of compositionally complex M5 Si3 silicides is synthesized. V5 Si3, Cr5 Si3, Nb5 Si3, Ta5 Si3, and W5 Si3 are all stable in tetragonal structures. However, (V1/5 Cr1/5 Nb1/5 Ta1/5 W1/5 )5 Si3 forms a hexagonal structure. Cation ordering is found, suggesting [Nb1/2 (Cr/V)1/2 ]2 [(V/Cr)1/3 Ta1/3 W1/3 ]3 Si3 . Hexagonal (Ti1/5 Zr1/5 Nb1/5 Mo1/5 Hf1/5 )5 Si3 is also synthesized. Abstract: A new type of compositionally complex (medium- or high-entropy) M5 Si3 silicides is synthesized. Both (V1/5 Cr1/5 Nb1/5 Ta1/5 W1/5 )5 Si3 and (Ti1/5 Zr1/5 Nb1/5 Mo1/5 Hf1/5 )5 Si3 form single-phase homogenous solid solutions. Notably, (V1/5 Cr1/5 Nb1/5 Ta1/5 W1/5 )5 Si3 forms the hexagonal γ (D88 ) phase, while all its five constituent binary silicides, V5 Si3, Cr5 Si3, Nb5 Si3, Ta5 Si3, and W5 Si3, are stable in the tetragonal α (D8l ) or β (D8m ) phases. Annealing at 1600 °C demonstrates that this hexagonal γ phase is stable. Comparison of the experimental and calculated X-ray diffraction patterns, Rietveld refinements, and analysis of aberration-corrected scanning transmission electron microscopy high-angle annular dark-field images suggest cation ordering, which reduces the configurational entropy. This work expands the field of high-entropy and compositional complex ceramics by not only discovering a new compositionally complex silicide phase but also demonstrating cation ordering and unusual phase stability. These compositionally complex silicides can be combined with refractory high-entropy alloys to make the high-entropy counterparts to the Nb-silicide and Mo-Si-B composites. Graphical abstract: Image, graphical abstract